PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL DAN SOLVABILITAS TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2018) - Liany Gozali; Karina Harjanto (Universitas Multimedia Nusantara, 2020)
The purpose of this research is to obtain empirical evidence about the effect of profitability, firm size, institutional ownership, and solvability towards audit delay. Dependent variable in this research is audit delay, and independent variables are profitability, firm size, institutional ownership, and solvability. The profitability was measured by return on asset (ROA), firm size was measured by natural logarithm (ln) total asset, institutional ownership was measured by number of shares owned by institution divided by outstanding share, and solvability was measured by debt to total asset ratio (DAR). The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sample of this research was selected by using purposive sampling method. Secondary data taken from annual report and financial report also analyzed by using multiple regression method. There are 21 manufacture firms selected as sample that had been listed on the IDX since 2015-2018. The result of this research are (1) profitability has no effect toward audit delay, (2) firm size has effect toward audit delay, (3) institutional ownership has effect toward audit delay, (4) Solvability has no effect toward audit delay, (5) profitability, firm size, institutional ownership, and solvability simultaneously have effect toward audit delay. Keywords: Audit delay, Firm Size, Institutional Ownership, Profitability, Solvability